The Language of Europe. Multilingualism and Translation in the EU Institutions: Practice, Problems and Perspectives - Barroso, José Manuel (European Studies, 2014)
This book offers a clear and comprehensive introduction to the policy area of multilingualism and to translation practice within the EU institutions.